2019
DOI: 10.1242/dev.178863
|View full text |Cite
|
Sign up to set email alerts
|

Spherical spindle shape promotes perpendicular cortical orientation by preventing isometric cortical pulling on both spindle poles during C. elegans female meiosis

Abstract: Meiotic spindles are positioned perpendicular to the oocyte cortex to facilitate segregation of chromosomes into a large egg and a tiny polar body. In C. elegans, spindles are initially ellipsoid and parallel to the cortex before shortening to a near-spherical shape with flattened poles and then rotating to the perpendicular orientation by dyneindriven cortical pulling. The mechanistic connection between spindle shape and rotation has remained elusive. Here, we have used three different genetic backgrounds to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…knl-1,3(kd) spindles frequently had two or more bivalents stacked end to end along the pole-to-pole axis of the spindle ( Fig. 3 A ) as previously described ( Vargas et al, 2019 ). Finally, knl-1,3(kd) spindles did not have apparent microtubule-free channels oriented in the pole-to-pole axis ( Fig.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…knl-1,3(kd) spindles frequently had two or more bivalents stacked end to end along the pole-to-pole axis of the spindle ( Fig. 3 A ) as previously described ( Vargas et al, 2019 ). Finally, knl-1,3(kd) spindles did not have apparent microtubule-free channels oriented in the pole-to-pole axis ( Fig.…”
Section: Resultssupporting
confidence: 66%
“…Because Dumont et al (2010) found that GFP::KNL-3 remained in kinetochore cups after knl-1(RNAi) , we chose to double deplete KNL-1 and KNL-3 to more completely reduce kinetochore function during meiosis. Two previously described methods were used, auxin-induced degradation in strains with auxin-induced degrons (AIDs) appended to the endogenous knl-1 and knl-3 genes and GFP(RNAi) on strains with GFP appended to the endogenous knl-1 and knl-3 genes ( Vargas et al, 2019 ). After 48-h RNAi, GFP fluorescence was not observed around chromosomes in living embryos ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLS-2 might promote oocyte contractile ring assembly and ingression more directly, through its regulation of microtubule stability during spindle assembly. Astral microtubules associated with this acentrosomal spindle are small and limited in number, but a recent study has proposed that they nevertheless can interact, through dynein, with cortical microtubules to engage pulling forces that move the spindle toward the cortex and rotate it from its initial parallel orientation relative to the oocyte cortex to a perpendicular orientation during polar body extrusion [ 60 ]. Astral microtubule interaction with the cortex might then also influence contractile ring assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Key questions in meiotic research regarding the mechanism, function, and regulation of chromosome pairing, telomere bouquet formation, CO formation, and spindle formation have since then been assessed by live-cell imaging, which has provided new insights. These studies included further analyses in fission yeast (Tomita and Cooper, 2007), budding yeast (Conrad et al, 2008;Koszul and Kleckner, 2009;Lee et al, 2012Lee et al, , 2020, and Drosophila (Hughes et al, 2011;Colombié et al, 2013;Christophorou et al, 2015), as well as C. elegans (Vargas et al, 2019), and mammalian cells (Schuh and Ellenberg, 2007;Kitajima et al, 2011;Holubcová et al, 2013;Lee et al, 2015;Pfender et al, 2015;Kyogoku and Kitajima, 2017;Mogessie and Schuh, 2017;Enguita-Marruedo et al, 2018;Nikalayevich et al, 2018;Silva et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%